2016
DOI: 10.12800/ccd.v11i31.643
|View full text |Cite
|
Sign up to set email alerts
|

Differences of muscular performance between professional and young basketball players

Abstract: High performance in a vertical jump, ability to repeat short sprints (RSA) and muscle power are all three most relevant factors for professional basketball players. Still, there is a lack of studies analyzing the differences of these variables between professional and young basketball players. The aim of this research is to study the differences on the vertical jump, the RSA and mechanical power between professional and elite young basketball players. For this, 11 professional (n = 11, age = 24.3 ± 5.5 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…There is a paucity of literature analysing the differences in muscle capacity between junior and senior elite basketball players, especially regarding the upper body. A previous study reported that senior basketball players produce significantly higher absolute power with lower extremities [21]. Our data suggest that there is no difference in neuromuscular quickness (as tested by k RTD-SF ), between juniors and seniors.…”
Section: Discussionsupporting
confidence: 54%
“…There is a paucity of literature analysing the differences in muscle capacity between junior and senior elite basketball players, especially regarding the upper body. A previous study reported that senior basketball players produce significantly higher absolute power with lower extremities [21]. Our data suggest that there is no difference in neuromuscular quickness (as tested by k RTD-SF ), between juniors and seniors.…”
Section: Discussionsupporting
confidence: 54%
“…Both indoor training and seasonal variation are associated with low sun and ultraviolet (UVB) exposure, the main source from which the body synthesizes this vitamin [56]. It seems important, therefore, to monitor 25(OH)D concentrations throughout the basketball season in order to mitigate any potential effects that this insufficiency may cause for the players, despite the fact that these are initial stages in which they are still training and competing quite below the level of professional athletes [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Brief maximal intensity efforts synonymous with open skill team sports will require significant energy contribution from the phosphagen pathways. 6 The phosphagen energy system is the predominant, although not exclusive, source of energy for maximal intensity actions lasting up to approximately six seconds 7 As most important actions in open skill sports are typically less than six seconds in duration, 8 the importance of phosphagen pathways to repeatedly provide energy for elite performance is apparent. The capacity of phosphagen energy system is limited by the rate at which phosphocreatine (PCr) can replenish ATP stores.…”
Section: Introductionmentioning
confidence: 99%